Digital Screening and Educational Interventions to Reduce Depressive Symptoms in Adolescents: a Scoping Review - Afifatul Mukaromah; Rizki Fitryasari P.K; Kristiawati Kristiawati (Jurnal Ners, 2025)
Introduction: Depression is a mental health disorder commonly found across all age groups, including adolescents. Adolescent depression imposes burdens on individuals, families, and caregivers and may lead to social, educational, occupational, and physical health problems. This study aimed to identify digital educational interventions to reduce depressive symptoms in adolescents. Methods: This study conducted a scoping review, analyzing articles from four academic databases: Scopus, Web of Science, PubMed, and Science Direct. Study selection was guided by the PCC (Population, Concept, Context) framework and followed the PRISMA-ScR reporting standards. Results: A total of 1,787 articles were identified, with 12 studies meeting the inclusion criteria. The review indicated that digital educational interventions can be categorized into three main approaches: (1) CBT-based interventions, (2) psychoeducation and self-management programs, and (3) chatbot- or social media–based interventions. Most interventions demonstrated significant reductions in depressive symptoms, anxiety, and improved resilience among adolescents. Several applications also integrated digital screening tools such as PHQ-8 and PHQ-9. Conclusion: Digital nursing interventions delivered through mobile health applications are effective in reducing depressive symptoms among adolescents. These interventions are innovative, scalable, and complement traditional mental health services by providing accessible, interactive, and youth-oriented approaches that address both psychological and physical needs.